MODAL SOSIAL DALAM BERTAHAN HIDUP PEKERJA MIGRAN NON PROSEDURAL ASAL KELURAHAN DABO LAMA, KECAMATAN SINGKEP, KABUPATEN LINGGA DI MALAYSIA - Vera Agustina; Suryaningsih; Casiavera (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Undocumented migrant workers are highly vulnerable to various risks due to their limited access to legal protection and social security in the host country. Under such circumstances, social capital serves as a crucial resource that enables them to sustain their livelihoods. This study aims to describe the role of social capital in the survival strategies of undocumented migrant workers originating from Dabo Lama Village, Singkep District, Lingga Regency, Indonesia, who are employed in Malaysia. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving purposively selected informants. The analysis was guided by Robert D. Putnam's theory of social capital, which emphasizes three key dimensions: trust, social networks, and norms. The findings reveal that social capital constitutes the primary resource that enables undocumented migrant workers to cope with the challenges arising from their irregular status. Trust established through relationships with family members, relatives, neighbors, friends, and fellow migrant workers facilitates access to employment opportunities, information, and assistance during difficult situations. Social networks function as important channels for obtaining jobs, accommodation, informal protection, and economic support while living in Malaysia. Meanwhile, shared norms of mutual trust, reciprocity, solidarity, and mutual assistance strengthen social cohesion and maintain sustainable social relationships among migrant workers. These three dimensions of social capital interact to form an adaptive mechanism that enables undocumented migrant workers to survive despite limited formal protection and the high risks associated with working in Malaysia.